Embarazo en adolescentes: conocimiento y actitudes Frente a los signos y síntomas de alarma en pacientes Atendidas en el puesto de salud punta del este, Julio-Diciembre 2015 - Altamirano Torres, Amparito (2016)
This study entitled "Teenage pregnancy: knowledge and attitudes about the signs And symptoms of alarm in patients treated at the Post Punta Health East, July- December 2015", quantitative, descriptive, correlational study, cross-sectional, Whose population and sample consisted of 98 pregnant teenagers. The Methodology was the survey and data collection instrument a questionnaire adapted From Flores, Ylatoma. The results were: 45.9% of pregnant adolescents are aged between 18 and 19 Years; 50% are cohabiting; 28.6% have completed primary school, 50.0% live with Their partners. 86.7% of pregnant teens had a pregnancy; 63.3% were between 21- 36 weeks of pregnancy. The most recognizable symptoms of alarm are: 47.0% (8) Pain or burning when urinating; 41.0% (7) headache or headache; 6.0% (1) Decreased fetal movements and 6.0% (1) uterine pregnancy or before 37 wk Contractions. As for the signs, 39.0% (9), fever or fever; also 39.0% (9) vaginal Bleeding; 14.0% (3) excessive nausea and vomiting; 4.0% (1) edema or swelling And 4.0% (1) hypertension or high blood pressure. Pregnant teenagers have a Medium level of knowledge and an indifferent attitude about warning signs and Symptoms of pregnancy. In conclusion the Middle East, is the level of knowledge of greater association with Attitudes towards signs and warning signs of pregnancy in pregnant adolescents Seen at the Post Punta Health East, July-December 2015, with a ratio of 5% Significance, X 2 = 90.192 and p = 0.000.